Pearls & Oy-sters: Vertical Diplopia and Ocular Torsion: Peripheral vs Central Localization. (2nd August 2022) - Shah, Manali; Primiani, Christopher T.; Kheradmand, Amir; Green, Kemar E.
Abstract : We describe a case with torsional deviation of the eyes from a brainstem lesion. Torsional eye movement refers to changes in the position of the eyes in the roll plane around the visual axis. When the head is tilted laterally (that is, rolled toward the shoulder), the eyes roll in the opposite direction as part of the torsional vestibulo-ocular reflex known as the ocular counter-roll. Pathologies that affect the otolith-ocular pathway can lead to a torsional deviation of the eyes as part of the ocular tilt reaction (OTR) that also causes vertical deviation of the eyes (skew deviation) and head tilt. Lesions caudal to the pontomedullary junction (such as the labyrinth, eighth cranial nerve, or vestibular nucleus) result in an OTR with ipsiversive torsional deviation, whereas lesions rostral to the junction result in an OTR with contraversive torsional deviation. Furthermore, torsional deviation of the eyes in the OTR is conjugate (incyclotorsion in the higher eye and excyclotorsion in the lower eye), whereas torsional deviation from ocular palsy in peripheral lesions is disconjugate (e.g., exyclotorsion only in the higher eye with superior oblique palsy). Therefore, the pattern of torsional eye deviation can be helpful in localizing the lesion. Several techniques including fundus photography, double Maddox rod testing, optical coherence tomography, and video-oculography are used to measure torsional eye position.